Literature Learning in The Digital Era: Challenges and Obstacles - Laila Tri Lestari; Novi Sriwulandari (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2023)
The digital era is characterized by the emergence of many technologies that serve to facilitate human life. Many social media are used in the scope of education. This convenience can be utilized by participants in expressing creativity in literature. This study aims to describe the obstacles in learning literature, solutions to deal with these obstacles, and how is learning literature in the digital era. This research used descriptive qualitative research method. The research data were presented in the form of descriptions. This research also uses interview techniques which contain the answers from the speakers then detailed by the researcher. Literature learning experiences several obstacles, obstacles occur from the educator and the students. The obstacles that occur researchers write some solutions to overcome them. Learning does not escape the evaluation process. In this case, the researchers discuss more about selective evaluation. Students' literary talents can be combined with developing technology. Usually using applications or mass media. Some of the mass media that can be utilized are Wattpad, Instagram, YouTube, blogs, spotify. From several choices of applications, it can be used for literature. Starting from oral literature to written literature.